Analysis of Home Assignments of students at the Primary Level An Evaluative Study - Bhatia, Kusum (JOURNAL OF INDIAN EDUCATION, 2014)
Home assignments (HA) are not meant to keep children occupied at home. These serve several educational needs which are essential to receive complete education. Practicing home assignments allow children to review what they have learnt in the class. Doing home assignments increases comprehension of a subject or topic by helping children retain it for a longer period of time. Extension of HA includes long term assignments such as small projects appropriate to the age and class of the children. If a teacher can create a desire to engage the children in activities and to participate in learning experiences, learning will become more functional and better designed to meet the objectives. An assignment denotes this aspect of teaching. To know how far teachers in primary schools have realised the potential of the assignment as an important part of teaching the present study was undertaken.